Status Sel Inflamasi dan Stadium Kanker Nasofaring di RS PKU Muhammadiyah Gombong - Oke Kadarullah; M. Nurrizki Haitamy; Andi Muh. Maulana (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2022)
Background: Nasopharyngeal cancer (NPC) is still a global health problem as well as in Indonesia. Patients come with an advanced stage which has a high impact on patient morbidity and mortality. The patient's prognosis is highly dependent on the supporting modalities to determine the stage. Supporting examinations with guiding standards are still limited, especially for hospitals in non-educational centers or not big cities. It is known that there is a close relationship between inflammation and a malignancy, especially NPC with risk factors for chronic viral infection. Objective: To see the role of easy and inexpensive routine blood tests to help assess the prognosis of NPC patients. Methods: Searching for secondary medical record data including histopathological data, CT Scan or physical examination or nasoendoscopy as well as routine blood laboratory data for NPC patients at PKU Muhammadiyah Gombong Hospital. Results: NPC patients were found with 100% non-keratinizing carcinoma-undifferentiated type,gender was male by 63% and in the most age range 46-65 years with advanced clinical stages reaching 66.7%. Inflammatory cell status includes a high neutrophil-lymphocyte cell ratio (NLR) of 70.4% and a high plateletlymphocyte cell ratio (PLR) of 62.8%. Conclusion: The most inflammatory cell status in NPC patients at PKUMuhammadiyah Gombong Hospital are high NLR and high PLR which are in line with the findings of high T stage and positive N (advanced clinical cancer stage).Latar belakang : Kanker nasofaring (KNF) masih menjadi permasalahan kesehatan dunia juga Indonesia. Pasien datang dengan stadium lanjut yang berdampak tingginya morbiditas dan mortalitas pasien. Prognosis pasien sangat tergantung modalitas penunjang guna menentukan stadium. Pemeriksaan pendukung dengan standar panduan masih bersifat terbatas terutama bagi rumah sakit di non sentra pendidikan atau bukan kota besar. Diketahui terdapat hubungan yang erat antara inflamasi dan suatu keganasan terutama KNF dengan faktor risiko infeksi virus kronik Tujuan : Untuk melihat peran pemeriksaan darah rutin yang mudah dan murah untuk membantu penilaian prognosis pasien KNF. Metode: Pencarian data skunder rekam medik meliputi data hasil histopatologi, CT Scan atau pemeriksaan fisik atau nasoendoskopi serta data laboratium darah rutin pasien KNF di RS PKU Muhammadiyah Gombong Hasil : Didapatkan pasien KNF dengan 100% tipe non keratinizing carcinoma-undifferentiated, jenis kelamin laki-laki sebesar 63% dan pada rentang usia terbanyak 46-65 tahun dengan stadium klinik lanjut mencapai 66,7%. Status sel inflamasi meliputi rasio sel netrofil-limfosit (NLR) tinggi sebesar 70,4% dan rasio sel trombosit-limfosit (PLR) tinggi mencapai 62,8%. Kesimpulan : Status sel inflamasi terbanyak pada pasien KNF di RS PKU Muhammadiyah Gombong adalah NLR tinggi dan PLR tinggi yang selaras dengan  temuan stadium T tinggi serta N positif (stadium kanker klinis yang lanjut).